2013
DOI: 10.2136/vzj2013.05.0080
|View full text |Cite
|
Sign up to set email alerts
|

Tritium Plume Dynamics in the Shallow Unsaturated Zone in an Arid Environment

Abstract: Effective isolation of tritium ( 3 H) and other contaminants at waste-burial facilities requires improved understanding of transport processes and pathways. Previous studies documented an anomalously widespread (i.e., theoretically unexpected) distribution of 3 H (>400 m from burial trenches) in a dry, sub-root-zone gravelly layer (1-2-m depth) adjacent to a low-level radioactive waste (LLRW) burial facility in the Amargosa Desert, Nevada, that closed in 1992. The objectives of this study were to: (i) characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…Maples et al . [] found that depletion of the gas‐phase tritium plume at the ADRS was greater than expected from standard estimates of diffusivity and radioactive decay. The high lateral diffusivity detected in the current tracer experiment may have contributed to mass‐loss from the plume.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Maples et al . [] found that depletion of the gas‐phase tritium plume at the ADRS was greater than expected from standard estimates of diffusivity and radioactive decay. The high lateral diffusivity detected in the current tracer experiment may have contributed to mass‐loss from the plume.…”
Section: Resultsmentioning
confidence: 95%
“…These equations have yielded feasible values of isotropic gas diffusivity in numerous experiments spanning small distances (e.g., 1 m) and time scales (hours to days) [ Werner et al ., ] as well as at larger vertical scales [ Weeks et al ., ]. Yet, some observations of lateral transport of gases in deep unsaturated sediments have been difficult to explain using mathematical and numerical models based primarily on diffusion with MQ‐type equations [ Striegl et al ., ; Mayers et al ., ; Walvoord et al ., ; Maples et al ., ]. Additional studies of vertical and lateral gas transport in deep unsaturated sediments are needed to better understand how broadly the common assumption of diffusive transport with MQ‐type relationships applies [ Weeks et al ., ; Carrigan et al ., ; Thorstenson et al ., ; Walvoord et al ., ; Walvoord et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Site operators excavated sediments, deposited waste, and backfilled the trenches. The unlined trenches received containers of solid waste, solidified liquid waste (in Portland cement), and some direct discharge of liquids (Striegl et al, 1996; Maples et al, 2013). The waste trenches ranged from 2 to 15 m deep.…”
Section: Methods: Field Site Sampling Analysis and Statistical Appmentioning
confidence: 99%
“…A 1‐yr controlled tracer test at the ADRS using SF 6 showed that gas diffusion was a primary transport mechanism at scales of tens of meters, and pronounced density effects were not observed (Walvoord et al, 2014). Studies of longer term transport of plumes at ADRS have indicated greater extents of contamination than expected from pure diffusion (Striegl et al, 1996; Mayers et al, 2005; Walvoord et al, 2008; Maples et al, 2013), possibly stemming from additional transport processes such as interactions of barometric pumping (advection) with geological layering (Green et al, 2015). The molecular mass of the gases influences the steady‐state vertical distribution of stable isotopes at the site (Seltzer et al, 2017).…”
Section: Methods: Field Site Sampling Analysis and Statistical Appmentioning
confidence: 99%
See 1 more Smart Citation